The Absurd In The Art Of Fluxus - عامر نعمة ايمان; naeeam mohan al waely, Tabarek (Journal of College of Education, 2020)
The current research dealt with the subject of the tag (works of tampering in the arts of phloxs), which specialized in studying the nature of the main concepts of tampering through an understanding of structural treatments and technical methods and the nature of raw materials and mechanisms of their work in artistic works of the art of phloxes, the research contained four chapters, the first chapter concerned: the methodological framework For research, represented by the research problem, which is determined by the following question: What are the works of tampering in the arts of Flexus? The second chapter also contained the importance of research and the need for it, by highlighting the idea of ​​tampering and its manifestation in the arts of the Flexus, and the goal of the research represented by (uncovering tampering in the arts of the Flexs), while the limits of the research were limited to studying the effects of tampering in the arts of the Flexes for a period of time (1960 -1990), specifically in the United States of America, in addition to defining terms in the research. As for the second chapter: it contained three sections that represent the theoretical framework consisting of the first topic philosophically. As for the second topic, which specialized in dealing with the absurd technically, the third topic deals with research in the arts of phloxs, as well as the indicators that the second chapter and previous studies have ended. As for the third chapter: it includes the research procedures represented by the research community and the sample represented by it, ending with the analysis of the sample of (3) samples with various technical works. As for the fourth chapter: It includes a set of results and conclusions, recommendations and proposals, and among the results reached by the researcher: 1- The artist’s feeling of incompatibility with the world / with a grudging attitude towards the surrounding things. 2- Artworks in the art of phloxation opposes logic by imparting mockery of its highest levels. As for the researcher’s findings, we mention: 1- The difference in the values ​​of art and beauty of the artist of the flexos. 2- The philosophical content of tampering is the real purpose and goal of the work of the Phloxs